Changes in the drug resistance of Staphylococcus aureus in a non-hospital population during a 20-year period - Goldie, D. J. (1971)
The antibiotic resistance of Staphylococcus aureus isolated in Bristol from primary skin sepsis and nasal carriers outside hospital was recorded between 1949 and 1969. The proportion of penicillinase-forming strains rose to about 60% but resistance to other antibiotics remained un-common except for a peak about 1957, due to the spread of multiresistant phage-type 80 staphylococci. Reasons are discussed for the failure of other multiresistant staphylococci to increase outside hospital. Recently isolated strains from inside and outside hospital were tested with sulphonamide and trimethoprim. All were sensitive to trimethoprim but 5% of non-hospital strains and 40% of hospital strains were resistant to sulphonamide. It is suggested that sulphonamide-resistant staphylococcal infections should not be treated with sulphonamide-trimethoprim mixtures because of the risk of breeding trimethoprim-resistant strains.